Genetic markers in Malaysians: variants of soluble and mitochondrial glutamic oxaloacetic transaminase and salivary and pancreatic amylase, phosphoglucomutase III and saliva esterase polymorphisms - Teng, Yao Sheng; Tan, Soon Guan; Lopez, C. G.; Ng, Thomas; Luang, Eng Lie-Injo (Springer, 1978)
Malaysians of Malay, Chinese, and Indian ancestries were electrophoretically phenotyped for Amy, and saliva esterase region 1(Set-i) from saliva, Amy1 from plasma, soluble and mitochondrial GOT and PGM3 from leukocyte and placenta. Kadazans and Bajaus, the indigenous people of Sabah, East Malaysia were surveyed for Amy2. Three types of variants were observed for Arny1, one type for Amy2. Only Indians were found to be polymorphic for Arny1. Two GOTs 2-1 and three GOTm 2-1 variants were found among 281 Chinese while three GOTm 2-1 variants were found among 311 Malays. Malaysian Malays, Chinese, and Indians were found to be polymorphic for Set-I and PGM3. The gene frequencies in Malays are Set-LF> 0.601 ± 0.021, Set-I S = 0.399 ± 0.021; PG1/3j = 0.788 ± 0.020, PGM~ = 0.212 ± 0.020; in Chinese set 1F = 0.497 ± 0.028, Set-I S = 0.503 ± 0.028; PGM1 = 0.745 ± 0.024, PGM~ = 0.255 ± 0.024; in Indians, Set-1F= 0.449 ± 0.031, Set-I S = 0.551 ± 0.031; PGM2/3 = 0.755 ± 0.029, PGM~ = 0.245 ± 0.029.